Eriocaulaceae from Serra da Canastra, Minas Gerais, Brazil - Mariane da Silva Freitas; Marcelo Trovó; Livia Echternacht (Rodriguésia)
Abstract Eriocaulaceae exhibit wide diversity within the Campo Rupestre, with the Serra do Espinhaço as their richest region. However, other mountain ranges featuring Campo Rupestre, like Serra da Canastra, also harbor a significant number of species. The present work consists of the taxonomic treatment of Eriocaulaceae occurring in the Serra da Canastra, as well as an analysis of the species distribution in three main surrounding Campo Rupestre areas: the Espinhaço and Mantiqueira Ranges, and the Chapada dos Veadeiros and neighbor mountains. Thirty-one species were recorded: 19 of Paepalanthus, six of Syngonanthus, four of Comanthera, one of Eriocaulon, and one of Leiothrix. Canastra shares eight species with Espinhaço, Mantiqueira, and Veadeiros; seven with Espinhaço and Mantiqueira; two with Espinhaço and Veadeiros; five exclusively with the Espinhaço and two exclusively with Veadeiros. Seven species are endemic to Canastra: Paepalanthus claussenianus, P. canastrensis, P. polycladus, P. sericiscapus, P. sinuosus, P. uai, and Syngonanthus culcitosus. Photographs, descriptions, identification key and comments on the morphological variations and geographic distribution for each species are presented, in addition to maps of the occurrence and distribution of species in different locations.